Build it! … but what if they don't come?. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of the paper is to address the issue of demand for broadband access and the specific role that bandwidth plays in this context. The aim is to assess available empirical evidence regarding the dynamics of bandwidth consumption in different countries and to discuss implications for public policy regarding the deployment of ultra‐fast broadband infrastructures, in particular vis‐à‐vis the Digital Agenda for Europe (DAE). Design/methodology/approach – The approach adopted uses publicly available empirical data in order to derive patterns of the development of broadband demand in previous years as well as regarding current demand in specific countries. The authors contrast these findings with information on the deployment of broadband infrastructures in these countries. Findings – The relationship between availability of fast broadband and the use of bandwidth by consumers appears to be richer and more complex than many have assumed. Availability of fast broadband does not alone appear to determine the level of use. This suggests that a more balanced approach between supply side and demand side measures is likely to be warranted. Originality/value – The paper provides new evidence on the relationship between the speed of fast broadband infrastructure and its use by consumers. Acknowledgements : Received 3 October 2013 Revised 3 October 2013 Accepted 18 October 2013. The authors would like to thank the participants of the 2013 EuroCPR Conference for their discussions, and two anonymous referees for their very helpful instructions to substantiate the arguments of the paper.